Muestra fotográfica para combatir la falsa percepción del rol de la mujer como bombero en la V Comandancia Departamental del Callao - Cortavarría Vidaurre, Valeria Lucía (2024)
Currently, women represent nearly 40% of the firefighter crew in the General Volunteer Fire Department of Peru (GVFDP). However, the low number of women who apply and remain in the GVFDP compared to men is possibly due to gender stereotypes and the misconception of the role of women that society has assigned them by culture and history. The Constitutional Province of Callao’s population is culturally considered a bit more macho, daring, urban, and conservative. A large part of the women firefighters are found in the companies of the Fire Department of Callao and are not immune to comments of rejection, discrimination, or surprise for their work, a job that could be stereotypically classified as masculine. In other words, female participation in firefighting is not yet fully normalized, despite years of progress in gender equality in the workplace. To fight the problem, using design and photography, a photographic exhibition is proposed in order to reinforce the image of women firefighters and make visible their ability to fulfill the functions of the firefighting service just like a man does. With this, it seeks to fight the false perception of the role that these women have in the GVFDP.